Thermal stability of phosphonic acid self-assembled monolayers on alumina substrates - Wan, Xianglong; Asyuda, Andika; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
Thermal stability of several representative self-assembled monolayers (SAMs) with phosphonic acid (PA) anchoring group on Al2O3 substrates was studied by in situ high resolution X-ray photoelectron spectroscopy, complemented by thermogravimetric analysis of the relevant bulk materials and theoretical simulations. The range of thermal stability and the degradation pathways were found to be dependent on the chemical composition of the SAM forming molecules, with backbone-specific “weak links”. Whereas the anchoring groups were hardly affected by annealing up to 773 K (highest temperature applied for most of the samples), temperature-induced breakup of the bond between the backbone and anchoring group or a specific bond within the backbone was observed. The former is the case for nonsubstituted alkyl backbone, which is cleaved at temperatures above 673-773 K (depending on the backbone length), with the subsequent desorption of the released fragments. The latter is the case for the substituted (pentafluorophenoxy) or partly fluorinated alkyl backbone, with the bond cleavage occurring at temperatures above 523 K, either between the substitution and alkyl linker or between the fluorinated and nonfluorinated segments of the backbone. The above results suggest a higher robustness and better thermal stability of PA monolayers as compared to other types of SAMs, such as thiolates on coinage metal substrates. It is however advisible to test thermal stability of a specifically designed, functional PA SAM in context of possible “weak links” as far as this is important for a particular application.